Optimizing Transportation Logistics through Enterprise Architecture: A Case Study of Integrated Management Systems - Bayu Yasa Wedha (Journal of Computer Networks, Architecture and High Performance Computing, 2023)
This abstract captures the essence of optimizing transportation logistics through Enterprise Architecture (EA) by presenting an Integrated Management Systems (IMS)-centered case study. Effective logistics management is crucial for enhancing operational effectiveness and attaining competitive advantages in today's rapidly changing business environment. Achieving this optimization, however, requires a comprehensive strategy that harmonizes disparate aspects such as operational processes, data administration, and technological infrastructure. This study demonstrates that Enterprise Architecture has the potential to function as the link between these domains. This study examines the difficulty of dispersed logistics operations and the resulting inefficiencies, cost escalation, and compromised responsiveness. The case study is presented as Integrated Management Systems powered by Enterprise Architecture principles. This integration intends to optimize workflows, encourage cross-functional collaboration, and provide real-time visibility into logistical activities. This investigation demonstrates how a well-designed EA framework can effectively mitigate transportation logistics and supply chain management disparities. By analyzing the results of the case study, this study aims to identify the benefits and challenges of implementing Enterprise Architecture within the realm of transportation logistics. This study explains how EA can improve operational efficiency, resource utilization, lead time, and customer satisfaction. Therefore, the research contributes to a broader comprehension of how Enterprise Architecture can optimally resolve the complexities inherent to contemporary transportation logistics. The potential for increased operational agility and competitiveness in the logistics industry is highlighted by applying EA principles to the context of integrated management systems.